2017
DOI: 10.16965/ijpr.2016.201
|View full text |Cite
|
Sign up to set email alerts
|

Trunk Muscles’ Response to Core Stability Exercises in Patients With Chronic Low Back Pain: A Randomized Controlled Trial

Abstract: Background: Core stability training has been widely advocated for management of patients with chronic low back pain to minimize attacks and as a preventive measure; however specific effects of this type of training are not fully investigated.Purpose: The purpose of this study was to investigate trunk muscles' response to core stability exercises in patients with chronic low back pain. Materials and Methods:Thirty male patients who had nonspecific chronic low back pain were randomly assigned to either core stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…This result implies that core stability exercise enhances abdominal muscle endurance in students of yoga and health department at the Faculty of Brahma Widya of UHN I Gusti Bagus Sugriwa Denpasar. The results of this study are also supported by some previous studies which demonstrated the effect of core stability exercise on abdominal muscle endurance (Aly, 2017;Tafakoriollah et al, 2020). The abdominal muscles consist of the abdominal rectus, internal and external oblique abdominals, and the traversal abdomen.…”
Section: Resultssupporting
confidence: 90%
“…This result implies that core stability exercise enhances abdominal muscle endurance in students of yoga and health department at the Faculty of Brahma Widya of UHN I Gusti Bagus Sugriwa Denpasar. The results of this study are also supported by some previous studies which demonstrated the effect of core stability exercise on abdominal muscle endurance (Aly, 2017;Tafakoriollah et al, 2020). The abdominal muscles consist of the abdominal rectus, internal and external oblique abdominals, and the traversal abdomen.…”
Section: Resultssupporting
confidence: 90%
“…In the second one ( Fig.no.2), the subjects were made to lie on the couch with both the calves resting on the ball and ask them to move the ball sideways while rolling the ball. In the third one ( Fig.no.3), subjects were made to lie on the couch with both the feet together resting on the ball and straightened the leg, In the fourth one ijlpr 2020; doi 10.22376/ijpbs/lpr.2021.11.1.L255-260 Physiotherapy L-257 ( Fig.no.4), the subjects were made to lie prone over the ball and asked to raise one leg and one arm in the alternate way 15,16 . All these exercises were maintained for 10 seconds and repeated 10 times.…”
Section: Methodsmentioning
confidence: 99%
“…These exercises are designed to enhance the ability of the neuromuscular and motor control systems to prevent spinal injury 12 .The conventional back care exercises decrease the pain and increase the strength of involved muscles, but results in frequent recurrence rates because of their effectiveness only up to one year and patients are left out with some residual pain and disability 2,4 .The conventional back exercises strengthen the involved muscles like the abdominals administering various back extension exercises like prone lying and lifting one leg, alternate leg and arm lifts, lifting upper trunk and both legs off the floor 2,4,13 . .The human spine buckles invitro during a compressive load of 90 N but the spine is loaded of about 4000 -6000 N, while administering various back extension exercises like prone lying and lifting one leg, alternate leg and arm lifts, lifting upper trunk and both legs off the floor 15 .The efficacy of general back exercises however, appears limited in achieving these goals 16 . Hence, the purpose of this study is to compare the effectiveness of core muscles activation over conventional exercises in reduction of pain and increasing Range of Motion of trunk in subjects with MLBP.…”
Section: Introductionmentioning
confidence: 99%
“…The above three processing methods can eliminate the size effect of data and classify the data into the same order of magnitude. 23,24 In the analysis, it is necessary to select a reasonable processing method according to the different characteristics of panel data, research purposes, and other available information such as indicators for non dimensional processing. Microsoft and Excel software were used to sort out the relevant data and charts of the paper, and SPSS17.0 statistical software was used to analyze the data before and after the experiment, so as to verify whether the experiment has significant effect.…”
Section: Comparative Analysismentioning
confidence: 99%